2020
DOI: 10.1111/liv.14516
|View full text |Cite
|
Sign up to set email alerts
|

First case of drug‐induced liver injury associated with the use of tocilizumab in a patient with COVID‐19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first discovered in Wuhan, China in 2019. The disease it causes (coronavirus disease-19-COVID-19) was officially named on 11 February 2019 by the World Health Organization. At the beginning of May 2020, there are nearly 230 000 cases of COVID-19-related deaths and around 3 267 000 cases confirmed worldwide (WHO: COVID-19 Situation report-103.) The pathophysiology of COVID-19 includes SARS-CoV-2 binding to the alveolar epithelium, thus activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 15 publications
(29 reference statements)
1
94
0
2
Order By: Relevance
“…5,7 The most common side effects of tocilizumab include headache and hypertension but, rarely, hepatotoxicity ranging from mild transaminases elevation to severe drug-induced liver injury (DILI) can occur. 8 Currently, data on hepatotoxicity of tocilizumab in COVID-19 disease are limited and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 The most common side effects of tocilizumab include headache and hypertension but, rarely, hepatotoxicity ranging from mild transaminases elevation to severe drug-induced liver injury (DILI) can occur. 8 Currently, data on hepatotoxicity of tocilizumab in COVID-19 disease are limited and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies in COVID-19 patients with tocilizumab (Klopfenstein et al, 2020;Luo P. et al, 2020;Toniati et al, 2020) and baricitinib (Cantini et al, 2020) have shown promising results. However, tocilizumab use requires caution in patients with hepatic impairment and can induce liver injury in some COVID-19 patients (Muhovic et al, 2020). The potential for additional opportunistic pulmonary infection is also associated with monoclonal antibodies such as tocilizumab.…”
Section: Sars-cov-2 and Raas Pathwaymentioning
confidence: 99%
“…Other drugs described as having the potential to cause hepatotoxicity in COVID-19 included hydroxychloroquine (n=1, 12.5%), tocilizumab (n=2, 25%), and remdesivir (n=1, 12.5%). 12,18,[54][55][56][57][58][59] The methodological characteristics of the finalised studies were also analysed. The largest number of the studies were retrospective observational studies (n=26, 41.9%), followed by meta-analyses (n=10, 16.1%), case reports (n=9, 14.5%), case series (n=7, 11.3%), prospective observational studies (n=3, 4.8%), and others Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…A number of drugs currently in use have hepatotoxic potential, which might be further exaggerated in the setting of chronic liver disease (CLD). 12,56,58 The mechanisms for individual drugs are not clearly defined.…”
Section: Drug-induced Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation